Numerical Study of the Ratio of Depth-to-Print Diameter on the Performance and Flow Characteristics for a Dimpled, Highly Loaded Compressor Cascade - Long Wang; Huawei Lu; Zhitao Tian; Yi Yang; Shuang Guo; Hong Wang; Xiaozhi Kong (Aerospace, 2022)
The influence of the ratio of dimple depth-to-print diameter (<semantics>λ</semantics>) on the highly loaded compressor cascade NACA0065-K48 is investigated based on the Reynolds-averaged Navier–Stokes (RANS) method. Simulations are conducted with a validated shear-stress transportation (SST) turbulence model coupled with the Gamma-Theta (<semantics>γ−Reθ</semantics>) transition model at the inlet Mach number of 0.7. At 5~25% of the axial chord on the suction surface, four rows of dimples are arranged in parallel, and the dimples’ spacing is 4 mm. Moreover, there are five kinds of <semantics>λ</semantics>, ranging from 0.125 to 0.875, which determine the pressed arc of a spherical dimple. Three flow regimes (diffuser–confuser flow, tornado-like vortex and horseshoe vortex) with the same topological structure are observed in these dimples, which affect the flow and performance of the cascade by changing the energy distribution. The distribution of turbulent kinetic energy (TKE) reflects the disturbance of the tornado-like vortex in the inferior arc dimples (<semantics>λ=0.375</semantics>) intensely, whereas the disturbance of the horseshoe vortex in superior arc dimples (<semantics>λ=0.625, 0.875</semantics>) is relatively weak. Numerical results indicate that the loss of the corner separation can be reduced with a dimples array, which is mainly related to the vertical climbing of the lateral flow that delays the starting point of the corner separation and weakens the mixing process. However, the loss in the wake of the dimpled cascades increases, which is caused by the thickened boundary layer induced by the high turbulent vortices. The dimpled cascade with <semantics>λ=0.625</semantics> can achieve the most significant loss reduction (13.47%), while ensuring the pressurization capacity.